For Church and Confederacy : The Lynches of South Carolina - Lynch (Family) (Book collections on Project MUSE., 2019)
"The Lynches of South Carolina were second-generation immigrants of parents with distinguished Irish roots who had come to America to restore the fortunes which religion and race had cost them in their occupied homeland. In the rising upcountry town of Cheraw Conlaw, Peter and Eleanor Neison Lynch quickly established themselves as leading citizens. The dozen children Eleanor successfully bore, however, were hardly conducive to the reacquisition of wealth. Of the twelve, five succumbed to tuberculosis, the disease that haunted the family. Of the seven survivors, five made exceptional marks in the careers they pursued, in medicine, manufacturing, and the religious life. Most notable was the eldest, Patrick Neison, who became the third Roman Catholic bishop of Charleston. Patrick developed a national reputation as a polemicist, preacher, and self-taught geologist. During the Civil War, Bishop Lynch proved to be the outstanding Catholic apologist for the Confederacy, a status that led Confederate officials to appoint him a special commissioner to the Papal States, in order to gain, if possible, the Church's recognition of the Confederate States, and with that recognition, the influence that might lead to European intervention"--